APLIKASI BIBLE PADA MOBILE PHONE DENGAN MENGGUNAKAN JAVA MICRO EDITION (JAVA ME) - Setiawan, Alexander; Noertjahya, Agustinus; Tjung, Eriek (Institute of Research and Community Outreach - Petra Christian University, 2009)
The Bible is a guidebook for the Christian life, the development of mobile technology allows to create applications Bible on mobile phones. This research aims to develop applications of existing Bible by providing new features. These features include, that can display two types of the same Bible (New International Version and the King James Version), features of note to the bookmark application, clear visibility on the in-verse bookmarks, display, grouping the bookmarks and search results clustering words, the application daily devotional, and maps. Database Bible is a database used Go Bible, and the search string using the Turbo Boyer Moore. Tests on the application made on the Nokia N78, Sony Ericsson W910i, K800 as a sample. From the results of testing, applications have been made to run well on all three mobile phone.